Bulk Ultrafine-Grained Interstitial-Free Steel Processed by Equal-Channel Angular Pressing Followed by Flash Annealing - Verma, Deepa; Pandey, Shobhit A.; Bansal, Anushka; Upadhyay, Shwetank; Mukhopadhyay, N.K.; Sastry, G.V.S.; Manna, R. (My University, 2016)
Interstitial-free steel workpieces are deformed by equal-channel angular pressing (ECAP) for equivalent strain εvm = 3 and εvm = 21 followed by flash annealing. Microstructures are analyzed by optical microscopy, scanning electron microscopy and transmission electron microscopy. Mechanical properties are evaluated by hardness testing. Yield strength of materials is calculated from hardness values. Flash annealing (at 675 °C) of ECAPed samples for εvm = 3 and εvm = 21 results in abnormal subgrain growth and abnormal grain growth, respectively. Flash annealing at 700 °C of ECAPed (at εvm = 3) IF steel converts abnormally grown subgrains to grains which serve as nuclei for recrystallization and that result in bimodal grain size distribution. Bimodal grain size distribution is also produced when ECAPed IF steel for εvm = 21 is flash annealed at 675 °C due to abnormal grain growth or secondary recrystallization. Flash annealing of IF steel samples ECAPed for low εvm, in the temperature range 600-675 °C, decreases the hardness continuously with increase in the annealing temperature but it increases at high εvm. The former is due to annihilation of defects but the later is caused by ordering of nonequilibrium boundaries. The hardening and strengthening behaviors are similar.
Keywords: ECAP; flash annealing; interstitial-free steel; scanning electron microscopy; transmission electron microscopy